Medical students and measuring blood pressure: Results from the American Medical Association Blood Pressure Check Challenge. Issue 6 (28th April 2017) - Rakotz, Michael K.; Townsend, Raymond R.; Yang, Jianing; Alpert, Bruce S.; Heneghan, Kathleen A.; Wynia, Matthew; Wozniak, Gregory D.
Abstract : Blood pressure (BP) measurement is the most common procedure performed in clinical practice. Accurate BP measurement is critical if patient care is to be delivered with the highest quality, as stressed in published guidelines. Physician training in BP measurement is often limited to a brief demonstration during medical school without retraining in residency, fellowship, or clinical practice to maintain skills. One hundred fifty‐nine students from medical schools in 37 states attending the American Medical Association's House of Delegates Meeting in June 2015 were assessed on an 11‐element skillset on BP measurement. Only one student demonstrated proficiency on all 11 skills. The mean number of elements performed properly was 4.1. The findings suggest that changes in medical school curriculum emphasizing BP measurement are needed for medical students to become, and remain, proficient in BP measurement. Measuring BP correctly should be taught and reinforced throughout medical school, residency, and the entire career of clinicians.